1976
DOI: 10.1152/ajplegacy.1976.230.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Electrical off response of cat esophageal smooth muscle: an analog simulation

Abstract: This investigation was performed to define characteristics and to design an electrical model of the slow membrane depolarization, or "electrical off response," that follows stimulation of cat circular esophageal smooth muscle. The electrical off response showed the following characteristics: 1) the response was preceded by hyperpolarization of the muscle membrane; 2) the amplitude of the off-response depolarization increased directly with increasing amplitude of the preceding hyperpolarization; 3) the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…5A). Similar inhibitory junction potentials have been reported previously for both vagal and field stimulation of cat and opossum esophageal tissue (4,7,11,12,22,25). A single long- The electrical responses to a long-duration stimulus were qualitatively similar to the 0.5-ms pulse but of greater magnitude (Fig.…”
Section: Spontaneous Activitysupporting
confidence: 84%
See 2 more Smart Citations
“…5A). Similar inhibitory junction potentials have been reported previously for both vagal and field stimulation of cat and opossum esophageal tissue (4,7,11,12,22,25). A single long- The electrical responses to a long-duration stimulus were qualitatively similar to the 0.5-ms pulse but of greater magnitude (Fig.…”
Section: Spontaneous Activitysupporting
confidence: 84%
“…Sarna et al (27) and Helm et al (18) have shown myogenic peristaltic contraction in the opossum in vivo and in vitro, respectively, but did not record the associated electrical events in their studies. However, a number of investigators have shown, usually in isolated strips, that esophageal circular (4,6,(21)(22)(23)27) and longitudinal (5,23) smooth muscle can be stimulated to produce repetitive electrical slow-wave-type activity with superimposed spike bursts and associated repetitive contractile activity. Progression of such combined electrical and mechanical activity along the esophagus was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the opossum and cat, unlike humans, administration of NO synthase blockers such as L ‐NAME and L ‐NMMA significantly reduced the amplitude of swallow‐induced oesophageal contractions 5 , 6 , 39 , 40 . These findings suggested that in some species, NO may have a partially excitatory effect either in the nuclei of the so‐called swallowing programme generator (SPG) in the brain stem, at the interneurone level, or peripherally at the muscle level, in which an initial NO‐dependent short hyperpolarization is followed by membrane depolarization and contraction (off response) 39–43 . The hyperpolarization and subsequent off response appear to be mediated by cGMP 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The question still unanswered is the relevance of the internal ganglionic interconnections of neurons versus a more myogenic control. Do muscle fibers affect adjacent fibers through a membrane or connective tissue connection to transmit an innate oscillatory pattern that is modulated by neural input (Chan and Diamant 1976)?…”
Section: Peripheral Neural Control Of Esophageal Peristalsismentioning
confidence: 99%